2003
DOI: 10.4161/cc.2.3.382
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Carcinogenesis: A Chain Reaction of Aneuploidizations

Abstract: Carcinogenesis is a multistep process in which new, parasitic and polymorphic cancer cells evolve from a single, normal diploid cell. This normal cell is converted to a prospective cancer cell, alias "initiated", either by a carcinogen or spontaneously. The initiated cell typically does not have a new distinctive phenotype yet, but evolves spontaneously-over months to decades-to a clinical cancer. The cells of a primary cancer also evolve spontaneously towards more and more malignant phenotypes. The outstandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
0
5

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(137 citation statements)
references
References 149 publications
(224 reference statements)
10
122
0
5
Order By: Relevance
“…This prediction has been confirmed previously by others [4,10,44,67,70,73,158,[166][167][168] including Boveri, who first demonstrated that X-rays, several chemicals, heat and physical stress generate aneuploidy, but failed to observe cancer in experimental animals [142,143]. However, since these studies did not establish pre-neoplastic aneuploidy as the cause of carcinogenesis [6,7,24,25], we have recently retested the question whether carcinogens cause aneuploidy experimentally, using mutagenic [84] and nonmutagenic carcinogens [169,170], and by reviewing the literature [4,10,25,73,158].…”
Section: Carcinogens Function As Aneuploidogenssupporting
confidence: 79%
See 2 more Smart Citations
“…This prediction has been confirmed previously by others [4,10,44,67,70,73,158,[166][167][168] including Boveri, who first demonstrated that X-rays, several chemicals, heat and physical stress generate aneuploidy, but failed to observe cancer in experimental animals [142,143]. However, since these studies did not establish pre-neoplastic aneuploidy as the cause of carcinogenesis [6,7,24,25], we have recently retested the question whether carcinogens cause aneuploidy experimentally, using mutagenic [84] and nonmutagenic carcinogens [169,170], and by reviewing the literature [4,10,25,73,158].…”
Section: Carcinogens Function As Aneuploidogenssupporting
confidence: 79%
“…However, since these studies did not establish pre-neoplastic aneuploidy as the cause of carcinogenesis [6,7,24,25], we have recently retested the question whether carcinogens cause aneuploidy experimentally, using mutagenic [84] and nonmutagenic carcinogens [169,170], and by reviewing the literature [4,10,25,73,158]. These tests have shown that mutagenic carcinogens generate aneuploidy either by breaking and rearranging chromosomal DNA or by chromosome nondysjunction owing to alterations of the spindle apparatus.…”
Section: Carcinogens Function As Aneuploidogensmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In addition, aneuploidy is a nearly ubiquitous feature of human cancers 3 and aneuploidy occurring in somatic cells is thought to play a key role in cancer development and/or progression. 4,5 In order to achieve correct chromosome segregation during mitosis, the sister kinetochores, multiprotein complexes that assemble on each chromatid of a replicated chromosome, must interact with microtubules coming from opposite spindle poles, so that the two sister chromatids can be pulled in opposite directions after anaphase onset. Upon nuclear envelope breakdown, dynamically unstable microtubules search the intracellular space until they encounter a kinetochore and capture it.…”
Section: Introductionmentioning
confidence: 99%
“…55 As more recently reported, 56 cancer appears to begin with epigenetic alterations in stem cells, thus implying that epigenetic (or non mutational) loss of gene expression comes more commonly before any mutations in cancer. 57,58 Also, Duesberg and colleagues [59][60][61][62][63][64][65][66] have heavily argued against the somatic mutation theory by definitely demonstrating that none of the predictions made by that theory is fulfilled by the evidence, 67 thus excluding any possible involvement of somatic mutation, and finally demonstrating and highlighting the fundamental role of aneuploidy in the genesis and progression of cancer. [68][69][70] Aneuploidy is a common feature in the majority of solid human cancers, and several tumour cell lines show chromosome instability (CIN).…”
Section: Discussionmentioning
confidence: 99%